Foliar Growth Regulator Sprays Induced Tolerance to Combined Heat Stress by Enhancing Physiological and Biochemical Responses in Rice - Pantoja-Benavides, Alvaro Daniel; Garces-Varon, Gabriel; Restrepo-Díaz, Hermann (Frontiers in Plant Science, 2021)
Rice yield has decreased due to climate variability and change in Colombia. Plant growth regulators have been used as a strategy to mitigate heat stress in different crops. Therefore, this study aimed to evaluate the effect of foliar applications of four growth regulators [auxins (AUX), brassinosteroids (BR), cytokinins (CK), or gibberellins (GA)] on physiological (stomatal conductance, total chlorophyll content, Fv/Fm ratio, plant canopy temperature, and relative water content) and biochemical (Malondialdehyde (MDA) and proline contents) variables in two commercial rice genotypes exposed to combined heat stress (high day and nighttime temperatures). Two separate experiments were carried out using plants of two rice genotypes, Fedearroz 67 (“F67”) and Fedearroz 2000 (“F2000”) for the first and second experiments, respectively. Both trials were analyzed together as a series of experiments. The established treatments were as follows: absolute control (AC) (rice plants grown under optimal temperatures (30/25°C day/nighttime temperatures), heat stress control (SC) [rice plants only exposed to combined heat stress (40/30°C)], and stressed rice plants and sprayed twice (5 days before and after heat stress) with a plant growth regulator (stress+AUX, stress+BR, stress+CK, or stress+GA). The results showed that foliar CK sprays enhanced the total chlorophyll content in both cultivars (3.25 and 3.65 mg g−1 fresh weight for “F67” and “F2000” rice plants, respectively) compared to SC plants (2.36 and 2.56 mg g−1 fresh weight for “F67,” and “F2000” rice plants, respectively). Foliar CK application also improved stomatal conductance mainly in “F2000” rice plants compared to their heat stress control (499.25 vs.150.60 mmol m−2s−1). Foliar BR or CK sprays reduced plant canopy temperature between 2 and 3°C and MDA content in plants under heat stress. The relative tolerance index suggested that foliar CK (97.69%), and BR (60.73%) applications helped to mitigate combined heat stress mainly in “F2000” rice plants. In conclusion, foliar BR or CK applications can be considered an agronomic strategy to help to ameliorate the negative effect of combined heat stress conditions on the physiological behavior of rice plants.